Investigating the role of sestrin 1 and sestrin 2 in preclinical models of tuberculosis disease - Naidoo, Saiyukthi (Department of Pathology, 2026)
Despite efforts to eradicate Tuberculosis (TB), Mycobacterium tuberculosis (Mtb), a causative agent for TB, can persist, and the emergence of drug resistance, emphasizes a dire need for new effective treatments and vaccine candidates. Recent understanding of TB immunology has shown hyperinflammatory responses causing damage to lung tissue structure and function, increasing pathology and severity of disease. This has sparked a search for anti-inflammatory modulators for Host Directed Therapies (HDT) to attenuate the effects of prolonged inflammation during chronic TB and persist after the completion of the therapy. Using Cap Analysis of Gene Expression (CAGE) transcriptomics, we identified a family of genes, Sestrins (Sesn 1 and Sesn 2), which showed differential expression after Mtb infection, particularly in Sesn1 where expression was significantly reduced, alluding to a possible role of Sestrins during TB disease. Sestrins are a family of antioxidant genes that have shown anti-inflammatory and metabolic modulatory roles in various disease models including cardiomyopathy, mitochondrial dysfunction, insulin resistance, and neurodegenerative diseases. However, the potential role of these genes remains unknown in TB, and conducting infection studies would contribute novel information to the TB field. By generating Sesn2 and macrophage-specific Sesn1 knockout mouse models, we uncovered the role of these genes for the first time in inflammation and TB disease. Here, we have shown that the deletion of Sesn1 (macrophage-specific) and Sesn2 (null) mice were undistinguishable from control animals at a naïve state. During TB disease, we demonstrate that global ablation of Sesn2 results in a significant increase in inflammation at later stage of Mtb infection and increased mortality. The increased inflammation was associated with enhanced total lung and lymph node cells, immune cell recruitment and lung tissue pathology. In contrast, macrophage-specific deletion of Sesn1 had no effect on the outcome of Mtb infection. To understand the mechanism, we found Sesn1- and Sesn2- deficient macrophages showed increased bacterial growth, pro-inflammatory response, and higher levels of cell death. We found reactive oxygen species, known to potentiate tissue damage, are associated with Sestrin ablation. Moreover, Sestrins are closely linked to metabolic regulation, Seahorse analysis showed that the absence of Sesn1 or Sesn2 hinders the ability of macrophages to regulate energy metabolism in the presence of stress, with higher ATP production rate and consistent energetic state, may result in elevated ROS levels. While our findings do not directly establish ROS as the primary driver of pathology in Sesn2 knockout mice, they suggest modulating inflammatory responses during TB disease.